Impact of economic sectors on inflation rate: Evidence from Ethiopia - Endashaw Sisay Sirah; Wondimhunegn Atilaw; Tecklebirhan Adisu (Cogent Economics & Finance, 2022)
It is unclear how sectoral growth in the agriculture, industrial, and service sectors affects inflation, and the topic is also quite rare. Accordingly, the researchers in this paper examine the long- and short-term effects of agriculture, service, and industry sectors on inflation rates. In order to achieve this, the researchers applied an autoregressive distributed lag model from 1975 to 2019. In order to determine the direction of causation, the Granger causality test was conducted. The results clearly demonstrate the negative relationship between agriculture, services, population, and inflation over the long term. In the short run, previous inflation, the service sector, the second lag in population, and the agricultural sector do not reduce inflation. The industrial sector and the first lag of the population can lower inflation rates. Thus, the industry sector in the long run and the service and agricultural sectors in the short run are inefficient at reducing inflation. Inflation and the agricultural sector are causally linked in both directions. Additionally, unidirectional causality runs from industry and the service sector to inflation. Early researchers have not examined the impact of the service, industry, and agriculture sectors on inflation rate, thus offering a unique contribution to policy makers. Panel data are not used to compare the sectoral responsibility for reducing inflation in other African countries with researchers. Practically, the agriculture and service sectors on the short run, along with the industry sector on the long run, both need attention.
Keywords: E23; E31; L8; Q1; 330; agriculture sector; Ethiopia; inflation rate; industry sector; service sector